Pengaruh Kesejahteraan Karyawan Terhadap Semangat Kerja Karyawan Pada Credit Union Sauan Sibarrung Tana Toraja - Paborong, Ratih; Bandhaso, Mira Labi; Rasinan, Djusniati (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This research aims to determine the significant influence of employee welfare on employee morale at the Sauan Sibarrung Tana Toraja Credit Union. The population in this research is employees who work at the Sauan Sibarrung Tana Toraja Credit Union. The number of samples in this study was 18 people from the entire population. Sampling was carried out by providing written statements or questions to respondents who worked at the Sauan Sibarrung Tana Toraja Credit Union so that they could be answered. The data analysis used is Spearman’s rank correlation coefficient analysis, coefficient of determination (r2), and t test. The research results show that the welfare provided significantly influences employee morale. Keywords: Employee Welfare, Word Morale